Preformulation studies of nefopam hydrochloride for physicochemical characterization and compatibility analysis with poly-3-hydroxybutyrate and poly-ε-caprolactone - S. NEELAM,; A. SANDEEP,; M. JITENDER, (International Journal of Pharma and Bio Sciences, 2017)
The objective of present investigation was to execute physicochemical characterization and compatibility analysis of nefopam hydrochloride (NPH) with poly-3-hydroxybutyrate (PHB) and poly-ε-caprolactone (PCL). Melting point and hygroscopicity assessment of NPH was performed by capillary and Ph. Eur. method, respectively. Residue on ignition (% ROI) was estimated as according to ICH Q4B R1. Drug-excipient compatibility was ascertained by differential scanning calorimetric. Melting point, % LOD and % residue on ignition of NPH was found 260 ± 5 °C, 0.27 % (≤ 0.5%) and 0.07 % (≤ 0.1%), respectively. Log P of NPH as determined by shake flask method was found 3.41. Numerous sharp crystalline peaks in x-ray diffraction pattern of NPH demonstrated highly crystalline characteristics. NPH was found freely soluble in acetone, soluble in water, ethanol, methanol and phosphate buffer pH 7.4 while very slightly soluble in chloroform and dichloromethane. Differential scanning calorimetry concluded compatibility between NPH, PHB and PCL.